TransModel: An R Package for Linear Transformation Model with Censored Data - Jie Zhou; Jiajia Zhang; Wenbin Lu (Journal of Statistical Software, 2022)
Linear transformation models, including the proportional hazards model and proportional odds model, under right censoring were discussed by Chen, Jin, and Ying (2002). The asymptotic variance of the estimator they proposed has a closed form and can be obtained easily by plug-in rules, which improves the computational efficiency. We develop an R package TransModel based on Chen's approach. The detailed usage of the package is discussed, and the function is applied to the Veterans' Administration lung cancer data.